2015
DOI: 10.5830/cvja-2015-034
|View full text |Cite
|
Sign up to set email alerts
|

Bare-metal stent thrombosis two decades after stenting

Abstract: Very late bare-metal stent (BMS) thrombosis is unusual in clinical practice. To the best of our knowledge, the latest that the thrombosis of a BMS has been reported is 14 years after implantation. Here, we describe a case of BMS thrombosis that occurred two decades after stenting. A 68-year-old male patient was admitted with acute anterior myocardial infarction. This patient had a history of BMS implantation in the left anterior descending coronary artery (LAD) 20 years previously. Immediate coronary angiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, this is the first case to report with the longest duration after bare metal stent implantation to thrombosis with an intravascular imaging guidance. Earlier, Acibuca and colleagues reported a case of BMS thrombosis occurring after two decades; however, in their report, intravascular ultrasound (IVUS) was not done and the exact duration was not clear [8]. Our case is unique as IVUS was performed and we demonstrated that multiple factors are responsible for plaque rupture leading to VLST such as (a) persistent peristent strut chronic inflammation leading to plaque rupture at the proximal stent edge, (b) neoatherosclerosis inside the stent which led to plaque rupture, and (c) the presence of calcium suggesting longer duration of the atherosclerotic plaque and subsequent plaque rupture due to a calcified nodule.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first case to report with the longest duration after bare metal stent implantation to thrombosis with an intravascular imaging guidance. Earlier, Acibuca and colleagues reported a case of BMS thrombosis occurring after two decades; however, in their report, intravascular ultrasound (IVUS) was not done and the exact duration was not clear [8]. Our case is unique as IVUS was performed and we demonstrated that multiple factors are responsible for plaque rupture leading to VLST such as (a) persistent peristent strut chronic inflammation leading to plaque rupture at the proximal stent edge, (b) neoatherosclerosis inside the stent which led to plaque rupture, and (c) the presence of calcium suggesting longer duration of the atherosclerotic plaque and subsequent plaque rupture due to a calcified nodule.…”
Section: Discussionmentioning
confidence: 99%
“…A stent is a medical insertion tool to facilitate the flow by insertion into a blood conduit or perfusion where foreign substances, such as cholesterol, are accumulated or the flow inside the human body is not smooth due to malignant tumors. Though the bare metal stent, which consists of a metal mesh structure, is the most basic structure, it is a structure in which foreign substances easily accumulate, and a restenosis problem may occur in which tissue in contact grows into the inside. For this reason, stent products are mainly coated stents. Silicone or e-PTFE is mainly used as the stent coating material, while polymer stents or drug-coated stents are also available. , However, each type of covered stent has its own problems. …”
Section: Introductionmentioning
confidence: 99%